Political Sociology: Theoretical Frameworks, Sociological Determinants, and Their Impact on Contemporary Public Opinion - Rajab Abdulsalam Alkhsah Alzarooq (Journal of Scientific and Human Dimensions, 2026)
In light of the outlined objectives, this research seeks to provide a comprehensive study of political sociology as an independent branch of the social sciences, highlighting its distinctive characteristics and scope of application that set it apart from other disciplines. The study traces the historical evolution of the concept of political sociology, from its classical intellectual roots to modern theories that have contributed to shaping the analytical framework for political and social phenomena. It also focuses on the theoretical analysis of issues related to this field, including developments in functionalist understanding, conflict theories, and social movements. Furthermore, it examines the determinants of political sociology, encompassing social, cultural, economic, and political factors. The research aims to clarify the field’s domain and its practical applications in analyzing political institutions, studying social mobility, and evaluating the dynamics of public opinion. Additionally, the study demonstrates the impact of political sociology in directing public opinion and understanding the socio-political processes associated with strategic decision-making within society. The study concludes with several findings, most notably that political sociology provides a profound understanding of the relationships between political institutions and social structures, linking them to economic and cultural forces. Collective identity and socio-economic transformations constitute essential factors in determining the form of social mobility and the level of participation in political processes. Moreover, protest and political inclinations can be explained by integrating class analysis with the study of cultural and political forces, illustrating the role of various social groups in shaping public opinion. Modern approaches have also shown that the digital space and social media platforms have become powerful tools in directing public opinion and social and political mobilization